A survey on the· occurrence of downy mildew and fusarium wilt on melon was conducted in Bogor and Sukabumi regions, from May 1983 to December 1984, which comprise of one wet season and one dry season. The areas surveyed were melon plantations in the districts of Cisarua, Cipayung, Ciawi, Caringin (Bogor region) and Parungkuda(Sukabumi region). The two diseases are considered as an important factor in melon production, because it could cause heavy losses. It was found that all farmer in the areas - A. Muin Adnan (Buletin Hama dan Penyakit Tumbuhan, 1986)
A survey on the· occurrence of downy mildew and fusarium wilt on melon was conducted in Bogor and Sukabumi regions, from May 1983 to December 1984, which comprise of one wet season and one dry season. The areas surveyed were melon plantations in the districts of Cisarua, Cipayung, Ciawi, Caringin (Bogor region) and Parungkuda(Sukabumi region). The two diseases are considered as an important factor in melon production, because it could cause heavy losses. It was found that all farmer in the areas surveyed planted the same variety, Sky Rocket 221, which was imported from Taiwan. The average infection intensities of downy mildew in the areas surveyed were not significantly different in both seasons, i.e., 24.56% in the wet season and 20.40% in the dry season. However, the average infection intensity of fusarium wilt was higher in the dry season (6.47%) than in the wet season (0.58%). The possible causes of the infection differences are discussed.